The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3390/membranes14040083
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Modification of Dialysis Membranes Sustains Middle Molecule Removal and Filtration Characteristics

Adam M. Zawada,
Karlee Emal,
Eva Förster
et al.

Abstract: While efficient removal of uremic toxins and accumulated water is pivotal for the well-being of dialysis patients, protein adsorption to the dialyzer membrane reduces the performance of a dialyzer. Hydrophilic membrane modification with polyvinylpyrrolidone (PVP) has been shown to reduce protein adsorption and to stabilize membrane permeability. In this study we compared middle molecule clearance and filtration performance of nine polysulfone-, polyethersulfone-, and cellulose-based dialyzers over time. Protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(224 reference statements)
0
0
0
Order By: Relevance
“…As investigational device, the trial included the novel FX CorAL dialyzer, which contains a hydrophilic membrane with increased PVP content on the blood-side surface. This study supports recent experimental studies which showed a strong correlation of hydrophilic membrane modification with reduced protein fouling, stabilized performance over time and the favorable hemocompatibility profile [ 9 , 10 , 17 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As investigational device, the trial included the novel FX CorAL dialyzer, which contains a hydrophilic membrane with increased PVP content on the blood-side surface. This study supports recent experimental studies which showed a strong correlation of hydrophilic membrane modification with reduced protein fouling, stabilized performance over time and the favorable hemocompatibility profile [ 9 , 10 , 17 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…To overcome hydrophobicity, these membranes are often blended with hydrophilic polyvinylpyrrolidone (PVP). Increased PVP content on the membrane’s blood-side surface reduces protein adsorption to the membrane, and associates with positive effects on hemocompatibility and performance [ 9 17 ].…”
Section: Introductionmentioning
confidence: 99%